Exploring learner identity in the blended learning context: A case study of collaborative writing. (August 2022) - Chen, Jing; Tan, Jie; Lei, Jun
Abstract: While there has been much research on language learner identity in traditional face-to-face classrooms, less attention has been paid to learner identity construction and its influencing factors in the blended learning environment. To bridge this gap, this study adopted a case-study approach to investigate six Chinese university students' learner identities constructed in the online and offline sessions of a blended English for academic purposes (EAP) course focusing on collaborative writing. Data included class observations and recordings, history logs on the writing platform, and semi-structured interviews. Different types of learner identities were identified from participants' verbal characteristics in offline classroom discussions (i.e., Group Leader, Spokesperson, Summarizer, and Follower) and from their writing revisions on the online writing platform (i.e., Industrious Contributor, Prudent Reader, Procrastinator, and Cooperative Writer). Both individual and contextual factors were found to influence the construction of learner identity in the blended learning environment for collaborative writing. The study also found that some students maintained their learner identities across the two cohesive learning sessions of the blended course whereas others did not. These findings provide implications for course design, pedagogical practice, and materials development. Highlights: Learner identity (LI) construction in blended collaborative writing was examined. Various LIs were identified in the online and offline sessions of blended learning. LI construction displayed different patterns across the online and offline sessions. Both individual and contextual factors influenced LI construction.